The Challenges for Green Energy in Romania under Current Energy Crisis - Andreea-Emanuela Drăgoi; Paul Calanter; Mihaela Gramaticu; Alina Dumitrescu; Alina-Cerasela Aluculesei (Amfiteatru Economic, 2023)
This paper aimed to evaluate the impact of the current EU energy crisis on Romania s policies to boost green energy as a solution to balance the national energy mix. Our methodological approach was a mixed one using both bibliometric analysis and qualitative analysis based on experts interview. The bibliometric analysis has included 1085 research papers from the WOS database and indicates the main research focus at the international level in the green energy field. The second part of the study was based on 6 interviews with Romanian experts in the energy field (selected from a larger group according to their expertise of more than 10 years in fundamental research and their involvement in public policies and national strategies in the energy field). The interviews aimed to investigate the national opportunities to adopt green energy practices at affordable prices. Our research has highlighted that many of the international research trends investigated by researchers are similar to those indicated by the Romanian experts. Our main finding showed that although Romania has performed better than most European countries in increasing the renewable energy share in the national mix, there is still untapped potential in the field. However, Romania has several particularities, according to the interviews results, such as the national regulation, geographical potential, and the existing infrastructure. To fully develop green energy (according to the objectives of RePowerEU and Green Deal), Romania must better tailor its national policy, while providing a stable and predictable legal framework and increased subsidies for green energy.
Keywords: P18; P48; P49; Q4; Q42; Q48; Q49; 330; green energy; Romania; RePowerEU; Green Deal